2022
DOI: 10.1016/j.isci.2021.103605
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular IL-32 regulates mitochondrial metabolism, proliferation, and differentiation of malignant plasma cells

Abstract: Summary Interleukin-32 (IL-32) is a nonclassical cytokine expressed in cancers, inflammatory diseases, and infections. Its expression is regulated by two different oxygen sensing systems; HIF1α and cysteamine dioxygenase (ADO), indicating that IL-32 may be involved in the response to hypoxia. We here demonstrate that endogenously expressed, intracellular IL-32 interacts with components of the mitochondrial respiratory chain and promotes oxidative phosphorylation. Knocking out IL-32 in three myeloma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 65 publications
(81 reference statements)
0
20
0
Order By: Relevance
“…We previously showed that IL-32 is upregulated upon relapse and that some IL-32-non-expressors start to express IL-32 in the time period between diagnosis and relapse ( 5 ). To investigate if TLR expression in a similar manner is increased in samples obtained at relapse compared with samples obtained at diagnosis we analyzed the same longitudinal RNA-sequenced samples (n=47).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that IL-32 is upregulated upon relapse and that some IL-32-non-expressors start to express IL-32 in the time period between diagnosis and relapse ( 5 ). To investigate if TLR expression in a similar manner is increased in samples obtained at relapse compared with samples obtained at diagnosis we analyzed the same longitudinal RNA-sequenced samples (n=47).…”
Section: Resultsmentioning
confidence: 99%
“…RNA sequencing data from CD138 + cells were available for 795 baseline samples from patients with MM. For TLR gene expression analysis, patient samples taken at diagnosis were divided into high and low IL-32 expression based on the same percentiles (upper 10 th and lower 90 th ) as used in our previous study on IL-32 in myeloma ( 5 ). We used the upper 10th percentile (n = 54; counts per million (cpm, log2)> 1.52) and lower 90th percentile (n = 741, (cpm,log2)≤ 1.52) and significance was analyzed by one-tailed Wilcoxon signed-rank test in R. Pearson correlation analysis was performed using stat_cor function in R.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations